Social value and individual choice: The value of a choice‐based decision‐making process in a collectively funded health system. (4th October 2017) - Espinoza, Manuel Antonio; Manca, Andrea; Claxton, Karl; Sculpher, Mark
Abstract: Evidence about cost‐effectiveness is increasingly being used to inform decisions about the funding of new technologies that are usually implemented as guidelines from centralized decision‐making bodies. However, there is also an increasing recognition for the role of patients in determining their preferred treatment option. This paper presents a method to estimate the value of implementing a choice‐based decision process using the cost‐effectiveness analysis toolbox. This value is estimated for 3 alternative scenarios. First, it compares centralized decisions, based on population average cost‐effectiveness, against a decision process based on patient choice. Second, it compares centralized decision based on patients' subgroups versus an individual choice‐based decision process. Third, it compares a centralized process based on average cost‐effectiveness against a choice‐based process where patients choose according to a different measure of outcome to that used by the centralized decision maker. The methods are applied to a case study for the management of acute coronary syndrome. It is concluded that implementing a choice‐based process of treatment allocation may be an option in collectively funded health systems. However, its value will depend on the specific health problem and the social values considered relevant to the health system.